2014
DOI: 10.1113/jphysiol.2014.284711
|View full text |Cite
|
Sign up to set email alerts
|

Human cerebrospinal fluid increases the excitability of pyramidal neurons in the in vitro brain slice

Abstract: Key pointsr The cerebrospinal fluid contains numerous neuromodulators at ambient levels but whether, and how, they affect the activity of central neurons is unknown.r This study provides experimental evidence that human cerebrospinal fluid (hCSF) increases the excitability of hippocampal and neocortical pyramidal neurons.r Hippocampal CA1 pyramidal neurons in hCSF displayed lowered firing thresholds, depolarized resting membrane potentials and reduced input resistance, mimicking properties of pyramidal neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 27 publications
5
53
1
Order By: Relevance
“…In contrast to synaptic transmission, where communication is discrete and dependent on neuroanatomical connections, CSF transmission of neuropeptides and small molecule neurotransmitters represents a neuroendocrine-like method of humoral transmission with the potential for widespread neuromodulation of distal regions of the brain (Veening and Barendregt, 2010). Indeed recent findings show that unidentified neuromodulators are present in human CSF in sufficient quantities to excite neurons, thereby supporting the plausibility of CSF transmission as a mechanism for system-wide modulation of neuronal activity (Bjorefeldt et al, 2015). However, the physiological contribution of CSF transmission to regulating behavior has remained hypothetical and largely understudied, possibly due in part to the technical challenge of separating the effects CSF-mediated signaling from concurrent synaptic transmission.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast to synaptic transmission, where communication is discrete and dependent on neuroanatomical connections, CSF transmission of neuropeptides and small molecule neurotransmitters represents a neuroendocrine-like method of humoral transmission with the potential for widespread neuromodulation of distal regions of the brain (Veening and Barendregt, 2010). Indeed recent findings show that unidentified neuromodulators are present in human CSF in sufficient quantities to excite neurons, thereby supporting the plausibility of CSF transmission as a mechanism for system-wide modulation of neuronal activity (Bjorefeldt et al, 2015). However, the physiological contribution of CSF transmission to regulating behavior has remained hypothetical and largely understudied, possibly due in part to the technical challenge of separating the effects CSF-mediated signaling from concurrent synaptic transmission.…”
Section: Discussionmentioning
confidence: 84%
“…We first examined the effect of hCSF on KA‐induced gamma oscillations in CA3 stratum pyramidale (Figure ), a well‐established method for studying these oscillations in vitro (Fisahn, ). Previous work has shown that hCSF increases the excitability of both hippocampal pyramidal cells (Bjorefeldt et al, ) and interneurons (Bjorefeldt et al, ), raising the possibility that synchronized neuronal activity might be promoted. Step application of 25, 35, and 45 nM KA to aCSF (of matched composition with regard to hCSF, see Methods) successively evoked gamma oscillations of increasing power from 1.33 ± 0.11 × 10 −09 V 2 to 4.13 ± 0.11 × 10 −09 V 2 ( n = 9, p < .001, One‐way repeated measures ANOVA with Sidak's multiple comparisons test, Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Part of the pooled hCSF was refrozen at a −80°C and kept at the Sahlgrenska Academy in Gothenburg to be used in whole‐cell patch clamp recordings. Electrolyte and glucose concentrations, as well as pH and osmolality, were measured according to methodology described in Bjorefeldt et al (). A matched aCSF was then prepared based on measured hCSF values, and used as control.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative would be to establish a reliable spikelet model in vitro . We propose to recreate in vitro a state of a pyramidal cell that retains the in vivo properties of sodium channels, for example by prolonged stimulation with fluctuating inputs and/or application of relevant neurotransmitters and neuromodulators naturally present in the cerebrospinal fluid in vivo [48]. Additionally, it might be necessary to record from neurons located in the middle of a slice, to minimize the dendritic loss and the resulting decrease in the somato-dendritic current sink.…”
Section: Discussionmentioning
confidence: 99%